The Evaluation of Petro-physical and Geological Properties of the Southern Asmari Reservoir / Fauqi oil field Southeastern Iraq - Al-Saad, Huda F.; Al-Shahwan, Muwafaq F. (Journal of Petroleum Research and Studies, 2019)
The wire line logs of five wells from Fauqi field are studied to delineate petro-physical properties, and also the shale volume and porosities are calculated and corrected from the effect of shale in this work. It is found that the formation of water resistivity is equal to 0.0145 Ω. m, which is calculated from the SP method (through the relationship between SSP and Rw). It is observed that the type of crude oil of the Asmari reservoir in Fauqia oil field is heavy. The Four units of oil reservoir within the Asmari Formation penetrated by the wells are delineated: A-B1-B2-C. The case study shows that the units (B1, B2) belongs to the formation of the upper Kirkuk, which is one of the main reservoir units producing oil in Asmari